2023
DOI: 10.1172/jci.insight.170199
|View full text |Cite
|
Sign up to set email alerts
|

AAV-mediated delivery of secreted acid α-glucosidase with enhanced uptake corrects neuromuscular pathology in Pompe mice

Abstract: Gene therapy is under advanced clinical development for several lysosomal storage disorders. Pompe disease, a debilitating neuromuscular illness affecting infants, children, and adults with different severity, is caused by a deficiency of lysosomal glycogen-degrading enzyme acid α-glucosidase (GAA). Here, we demonstrated that adeno-associated virus–mediated (AAV-mediated) systemic gene transfer reversed glycogen storage in all key therapeutic targets — skeletal and cardiac muscles, the diaphragm, and the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…Recently, a study using a new adjunct therapy based on the enzyme and chaperone ATB200/AT222 combination showed enhanced efficacy over the currently approved ERT in Gaa -/mice. ATB200/AT222 was able to normalize muscle glycogen content and reduced the levels of lysosomal and autophagosomal markers in the muscle of Gaa -/mice to wild type levels 7,18 . Clinical trials of AT2221/ATB200 have been completed and this approved treatment now offers an alternative effective therapeutic option for Pompe disease patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, a study using a new adjunct therapy based on the enzyme and chaperone ATB200/AT222 combination showed enhanced efficacy over the currently approved ERT in Gaa -/mice. ATB200/AT222 was able to normalize muscle glycogen content and reduced the levels of lysosomal and autophagosomal markers in the muscle of Gaa -/mice to wild type levels 7,18 . Clinical trials of AT2221/ATB200 have been completed and this approved treatment now offers an alternative effective therapeutic option for Pompe disease patients.…”
Section: Discussionmentioning
confidence: 94%
“…Knocking down Gys1 led to restoration of muscle functionality in the Gaa -/- mouse model 17 . Similarly, intramuscular injection of recombinant adeno-associated virus-1 (AAV-1) vector expressing short hairpin ribonucleic acid (shRNA) targeted to Gys1 has been shown to reduce glycogen accumulation in the gastrocnemius of newborn Gaa -/- mice 18 . Altogether the preclinical evidence suggests that reducing GYS1 can be a potential therapeutic approach in Pompe disease, either alone or in combination with ERT.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this work experimentally confirmed the prediction that the reversal of lysosomal (primary abnormality) and autophagic (secondary abnormality) defects in the diseased muscle upon treatments would proceed in the same order. Indeed, the comparison of ATB200/AT2221 vs. alglucosidase alfa as well as systemic vs. liver-targeted gene therapy in KO mice demonstrated that complete/near complete glycogen clearance is a precondition for the buildup resolution [122,125]. The mechanism underlying the reversal of the autophagy defect is not exactly clear.…”
Section: Next-generation Enzyme Replacement Therapy: Effect On Autophagymentioning
confidence: 99%
“…To prove that the outcome of a given treatment can indeed be assessed by visualizing the extent of autophagic buildup, gastrocnemius muscle of GFP-LC3:KO was imaged following AAV-mediated systemic gene therapy. The exact same gene therapy in the original KO had been previously shown to reverse both lysosomal and autophagic defects in this tissue-a lengthy process that involved a range of biochemical/molecular biology methods to analyze the samples ex vivo [125].…”
Section: Relieving the Burden Of Autophagy As A Gauge Of Therapeutic ...mentioning
confidence: 99%
“… 1 Over the years, our studies using a mouse model (knockout [KO]) provided a large body of evidence indicating that: 1) the dysfunction of glycogen‐laden lysosomes leads to a major secondary abnormality in the diseased muscle – impaired autophagy and massive autophagic buildup; 2) the buildup resolution upon treatments occurs only when glycogen levels and lysosomal pool return to normal; and 3) the elimination of autophagic buildup is a reliable indicator of therapeutic efficacy. 2 , 3 , 4 …”
mentioning
confidence: 99%